ISLAMIC ECONOMIC STRATEGY FACES GLOBAL RECESSION IN THE PERSPECTIVE OF DAKWAH: STRATEGI EKONOMI ISLAM MENGHADAPI RESSESI GLOBAL DALAM PERSEPEKTIF DAKWAH - Agus, Agusman (Program Studi Pengembangan Masyarakat Islam STID Mohammad Natsir, 2023)
The threat of a global economic recession in 2023 is a concern for many countries, including Indonesia, which is affected by the continuing conflict between Ukraine and Russia. Food crises and budget deficits are serious problems in various countries today. The Financial Services Authority (OJK) reports that economic recessions generally occur when gross domestic product (GDP), unemployment rate, and economic growth decline for two consecutive quarters. In addition, inflation is inevitable, and central banks in various countries are also raising interest rates aggressively. All this resulted in major problems that would be difficult to overcome without the concept of Islamic economics. To understand the concept of Islamic economics, massive da'wah efforts by da'is are needed. They must continue to improve their understanding of Islam, both in terms of ubudiyah and muamalah. Their da'wah material is expected to be an inspiration and solution to overcome various problems faced by the people. The purpose of da'wah is to change people's attitudes and behavior for the better, both individually, family, and society, so that their way of thinking and way of life change for the better. In the economic context, the balance between supply and demand, the circulation of money as a medium of exchange, and the production activities of basic necessities are important keys. Islamic economic da'wah promotes this balance and promotes economic justice. The role of the Islamic economy is expected to be an intermediary in production activities, so that the real sector of the economy can run balanced and fair, even in the face of economic crisis or recession.